Improving Students’ Vocabulary Mastery through Teaching Real Objects - Puji Hariati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study was aimed to find out the improvement of the students’ vocabulary mastery through teaching real object. This study was conducted by using Classroom Action Research. It was done through 1) planning, 2) action, 3) observation, and 4) reflection. The population of the research was the students of Amik Medicom. To get the sample, the researcher took one class, it was MI18B. This research applied quantitative and qualitative data. Quantitative method were taken from the students' test. Qualitative data were taken from observation, questionnaires sheet and diary notes. The research found out that there are some improvements of the students’ vocabulary mastery taught by applying real objects. It was proved from the students’ improvement in cycle 1 until cycle 2. The improvement can be seen that in pre test the means score was 34.66. In the first cycle,  meeting 1 the means score was 37,33, in meeting 2 was 47,66 and in meeting 3 was 53,5. In the second cycle, meeting 1 the means score was 68,83,  in meeting 2 was 80,33 and in meeting 3 was 91,66. The improvement also can be seen from the percentage of the students’ achievement in mastering vocabulary; in pre test, no one of the students got 75 points. In the first cycle, in meeting 1, and there no one student got 75 point,  in meeting 3 there was 16.7% (5 students) got 75 points. It means there was an improvement about 16.7 % . In the second cycle, in meeting 1 there was 20% (6 students) got 75 points, it means that there was an improvement about 3.3%. In meeting 2 there was 80% (24 students) got 75 points, it means that there was an improvement about 70%.  In meeting 3 there was 100% (30 students) got up 75 points, it means that there was an improvement about 30%. It means that all of the students got better result. They could master many new vocabulary items and composed them into good sentences.